The natural rate of interest in Brazil between 1999 and 2005 - Barcellos Neto,Paulo Chananeco F. de (2009)
The aim of the present study is to estimate the level of the natural rate of interest in Brazil. First, statistical filters are used for the ex ante and ex post real interest series. Then, an estimation of a dynamic Taylor rule is performed. These two estimates are eventually compared with the natural rate of interest obtained from a simplified macroeconomic state-space model following Laubach and Williams (2003). The results indicate that monetary policy decisions caused the level of the real interest rate to fluctuate around the natural rate of interest, showing that the Brazilian monetary authority can not be characterized as conservative over the analyzed period.